Search Engine Marketing, Inc. : Driving Search Traffic to Your Company's Web Site, Second Edition - Moran, Mike; Hunt, Bill (IBM Press, 2008)
The #1 Step-by-Step Guide to Search Marketing Success ... Now Completely Updated with New Techniques, Tools, and Best Practices. "My copy of the first edition of Search Engine Marketing, Inc. is ratty and dog-eared from extensive use. It's full of coffee stains and my own scribbled notes. Because it so effectively demystifies search engine marketing and provides such practical advice for success, I turn to it again and again and recommend it to audiences worldwide. This book is not academic blather or geeky techno-speak; it's an approachable and digestible guide chock-full of real-life examples."--David Meerman Scott, Bestselling Author of The New Rules of Marketing and PR "Keeping pace with the rapidly changing search marketing landscape, the latest edition of Bill Hunt and Mike Moran's search industry bible, Search Engine Marketing, Inc., incorporates informative and enlightening sections on optimizing multimedia, improving Web site search, and the emergence of social media and what it really means to the search marketer. There is valuable information in this book to help inform at every level from the beginner who is curious about search to the advanced enterprise search marketer. Taking a very complicated, technical, and data-driven industry and making it easily understandable and actionable is no small task, and Search Engine Marketing, Inc.succeeds on every level. If you only read one book on search marketing principles and best practices, this is the one." -Jay Middleton Senior Manager, WW Search Marketing, Adobe Systems, Inc. "With Search Engine Marketing, Inc., Bill Hunt and Mike Moran have successfully updated what is already known in the industry as "The Search Marketing Bible." With new content, examples, and insight including social media and Web site search, this is a must read book for marketers at companies of all sizes from startups to the Fortune 100." -Lee Odden CEO of TopRank Online Marketing and Author of Online Marketing Blog In this book, two world-class experts present today's best practices, step-by-step techniques, and hard-won tips for using search engine marketing to achieve your sales and marketing goals, whatever they are. Mike Moran and Bill Hunt thoroughly cover both the business and technical aspects of contemporary search engine marketing, walking beginners through all the basics while providing reliable, up-to-the-minute insights for experienced professionals. Thoroughly updated to fully reflect today's latest ...